HUBUNGAN DUKUNGAN KELUARGA PASIEN TUBERKULOSIS PARU DENGAN KEPATUHAN MINUM OBAT DI PUSKESMAS PEKAUMAN BANJARMASIN - Ahla, Nazelia; Heriyani, Farida; Al Audhah, Nelly; Haryati, Haryati; Skripsiana, Nika Sterina (Homeostasis, 2024)
Abstract: Tuberculosis (TB) is an infectious disease that is still a matter of public health in the world. South Kalimantan is ranked tenth out of all provinces listed as the highest TB contributor area in Indonesia. Puskesmas Pekauman is the Puskesmas with the highest incidence of TB in Banjarmasin. Adherence to medication is an example of a factor that plays a role in the success of pulmonary TB control. Adherence to treatment requires social support that begins with family support. Family support is one of the factors that motivate pulmonary TB patients to be obedient in carrying out treatment. The purpose of this study was to determine the relationship between family support of pulmonary TB patients with adherence to taking medication at the Pekauman Banjarmasin Health Center. This study was observational analytic with a cross-sectional study design. The research subjects were selected using total sampling techniques during the study period, 45 samples were obtained that met the inclusion criteria. Data collection was conducted using family support questionnaires and compliance questionnaires. Data analysis was performed with Chi-square test ( =0.05). The results showed families supported 64.4%, families did not support 35%. The adherence of patients seeking treatment as much as 55.6% classified as compliant and 44.4% classified as non-compliant. The results of the Chi-square test obtained a value of ρ = 0.00 (ρ <0.05) which showed that there was a significant relationship between family support of pulmonary TB patients and adherence to taking medication. Keywords: family support, adherence, pulmonary TB, cummonity health center Abstrak: Tuberkulosis (TB) adalah penyakit infeksi menular yang masih merupakan perkara kesehatan masyarakat di dunia. Kalimantan Selatan menduduki peringkat kesepuluh dari seluruh provinsi yang terdaftar sebagai daerah penyumbang TB tertinggi yang ada di Indonesia. Puskesmas Pekauman merupakan Puskesmas dengan kejadian TB paling banyak di Banjarmasin. Kepatuhan minum obat adalah contoh faktor yang berperan dalam kesuksesan pengendalian TB paru. Kepatuhan dalam pengobatan memerlukan dukungan sosial yang bermula dari dukungan keluarga. Dukungan keluarga menjadi salah satu faktor yang memotivasi pasien TB paru untuk patuh dalam menjalankan pengobatan. Tujuan penelitian ini untuk mengetahui hubungan dukungan keluarga pasien TB paru dengan kepatuhan minum obat di Puskesmas Pekauman Banjarmasin. Penelitian ini bersifat observasional analitik dengan desain penelitian cross sectional. Subjek penelitian dipilih menggunakan teknik total sampling selama periode penelitian, didapatkan 45 sampel yang memenuhi kriteria inklusi. Pemungutan data dilakukan dengan menggunakan kuesioner dukungan keluarga dan kuesioner kepatuhan. Analisis data dilakukan dengan uji Chi-square ( =0,05). Hasil penelitian menunjukkan keluarga mendukung 64,4%, keluarga tidak mendukung 35%. Kepatuhan pasien berobat sebanyak 55,6% tergolong patuh dan 44,4% tergolong tidak patuh. Hasil uji Chi-square didapatkan nilai ρ = 0,00 (ρ <0,05) yang menunjukkan bahwa ada hubungan bermakna antara dukungan keluarga pasien TB paru dengan kepatuhan minum obat. Kata-kata kunci : dukungan keluarga, kepatuhan, TB paru, puskesmas